2011
DOI: 10.1111/j.1365-2591.2010.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of thermoplasticized and single point root fillings assessed by micro‐computed tomography

Abstract: All techniques produced comparable results in terms of percentage of filling and void distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
2
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 56 publications
6
109
2
13
Order By: Relevance
“…Lateral condensation is the oldest and still used technique, but it requires professional expertise and demands more time and material for its execution 2 . The thermoplasticized gutta-percha root canal obturation technique is one the most indicated because it is associated with better anatomic filling [3][4] and less quantity of sealer used [5][6][7] , but it lacks longitudinal control and needs special equipment 3 . In this way, the improvement of older and conventional techniques is aimed at enhancing practicality, rapidity and simplicity, which benefit both the patient and the dentist.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral condensation is the oldest and still used technique, but it requires professional expertise and demands more time and material for its execution 2 . The thermoplasticized gutta-percha root canal obturation technique is one the most indicated because it is associated with better anatomic filling [3][4] and less quantity of sealer used [5][6][7] , but it lacks longitudinal control and needs special equipment 3 . In this way, the improvement of older and conventional techniques is aimed at enhancing practicality, rapidity and simplicity, which benefit both the patient and the dentist.…”
Section: Introductionmentioning
confidence: 99%
“…Voids along the canal walls are caused by the presence of a gap between the filling material and the dentinal walls and may jeopardize the outcome, because they are in contact with potentially infected canal walls; furthermore, they represent a gap that may promote the failure of the sealer and lead to leakage. 15 Clinically, voids in root fillings are difficult to detect. 16 Many methods (dye penetration, fluid transport and crosssection analyses, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Although single-cone technique has been perceived to be less effective in sealing root canals than the gutta-percha warm vertical compaction technique [3], it has recently been revived with the introduction of greater taper master cones that closely match the geometry of nickel-titanium instrumentation systems [4]. Several studies reported that single-cone obturation technique had comparable results to the cold lateral compaction and the thermoplasticized gutta-percha techniques [5][6][7] whereas in other reports, single-cone obturation was found to result in inferior obturation [8][9][10]. The purpose of this study was to compare the long-term clinical and radiographic outcome of matched-taper single-cone filling technique versus gutta-percha warm vertical compaction technique.…”
Section: Introductionmentioning
confidence: 99%